First-time Glenohumeral Dislocations: Current Evidence and Considerations in Clinical Decision Making. Issue 4 (December 2020) - Kunze, Kyle N.; Cohn, Matthew R.; Williams, Brady T.; Garrigues, Grant; Chahla, Jorge
Abstract : The decision to manage first-time shoulder dislocations conservatively or operatively has become increasingly complex because of conflicting literature. Although shoulder dislocations have traditionally been managed with reduction and immobilization, recent evidence has suggested high rates of subsequent recurrence. Surgical intervention is thought to better restore stability and decrease recurrence rates; however, it also has the potential for additional morbidity and financial cost. As such, recent literature has sought to better define patient risk profiles to identify optimal candidates for both conservative and operative management. The purpose of the current review is to provide a comprehensive and evidence-based assessment of the most recent literature to better delineate an appropriate treatment algorithm for this challenging clinical scenario.